Analysis of malondialdehyde and ferric reducing ability of plasma in type 2 diabetes mellitus patients in Lucknow city, India - Mohammad Zaid Kidwai; Roshan Alam; Haseeb Ahsan; Mohammad Mustufa Khan; Saba Khan (Acta Biochimica Indonesiana, 2022)
Background: The incidence and prevalence of type 2 diabetes mellitus (T2DM) is increasing due to obesity and sedentary lifestyles. Increased oxidative stress leads to oxidative damage of biomolecules and decreased antioxidant capacity.Aim: The study was designed to determine the malondialdehyde (MDA) and ferric reducing ability of plasma (FRAP) in T2DM patients at IIMS&R Hospital, Lucknow.Method: The oxidative stress was analyzed in T2DM patients as MDA. The total antioxidant capacity was estimated through the FRAP in T2DM patients and control subjects.Results: The level of MDA was observed to be higher (4.84 ± 1.09) in T2DM patients compared to controls (2.20 ± 0.85). The FRAP was lower among T2DM patients (509.46 ± 126.36) compared to controls (895.62 ± 179.92). The difference between FRAP in T2DM patients and controls was statistically significant (p=0.0001).Conclusion: MDA was found to be higher in T2DM, and the FRAP level was lower in T2DM patients compared to controls, signifying increased oxidative stress and decreased antioxidant level in T2DM patients.